La seguridad industrial y salud ocupacional y su incidencia en el ámbito laboral de la empresa D’ ROLY de la ciudad de Quito, provincia de Pichincha, año 2023. - Guerron Lara, Anddy Vinicio (2024)
In this research work we analyzed which is the incidence of industrial safety and occupational health in the labor environment of the company, this research was carried out through different methodologies, including field research which allowed us to collect data directly from the company, According to the implemented surveys we obtained results where we analyzed the perceptions and needs of the workers of the company D'ROLY in relation to industrial safety and occupational health, and the interview with the owner who expressed that the company has a code of Safety and Hygiene, and the interview conducted with the owner who expressed his interest in the implementation of safety and health standards at work in his company, according to the hypothesis was based on a positive since D' Roly has the potential to generate a positive impact on the workplace, thus improving the safety of employees, increasing productivity, reducing costs and improving the work environment, while the negative hypothesis is not met because if the company did not implement a model of safety and occupational health would not have no end this research. And it has ended with the conclusions and recommendations that emerged during the development of this research.